Environmental and Health Consequences of Heavy Metals in Crude Oil-Polluted Soils in Ihwrekreka Community - Bankole, Adedoyin Olubunmi; Ogunkeyede, Akinyemi Olufemi; Adedosu, Taofik Adewale; Udeochu, Uche; Agboro, Harrison; Odoh, Benjamin Chinedu; Isimekhai, Khadijah Ateda; Isukuru, Efe Jeffery (Research Advances in Environment, Geography and Earth Science Vol. 8, 2024)
Crude oil pollution has caused severe environmental issues and health risks in the Niger Delta, particularly affecting indigenous communities. This study aims to characterize and quantify heavy metal contamination in the soils of the Ihwrekreka community, a region significantly impacted by crude oil pollution due to illegal refining and bunkering activities. Soil samples were collected and analyzed for heavy metals using inductively coupled plasma mass spectrometry (ICP-MS). The concentration ranges in mg/kg for metals found in the contaminated soil were 4.85–17,078 for copper (Cu), 1.01–16.1 for cadmium (Cd), 0.22–36.8 for chromium (Cr), 8.28–40.9 for nickel (Ni), 7.51–6,474 for lead (Pb), and 8.84–12,851 for zinc (Zn). These levels significantly exceed World Health Organization permissible limits, with Cu, Zn, and Pb identified as the most contaminating metals. A strong correlation (91.5%) was observed between Cr, Zn, and Ni, indicating the substantial contribution of crude oil pollution to heavy metal contamination in the soil. The hazard index for chromium indicates a high likelihood of adverse health effects from daily exposure. Elevated risk levels were also identified for zinc, copper, and lead. For example, hazard quotients for lead ingestion reached critical levels, with values up to 23.0 for children and 0.985 for adults. These findings highlight the urgent need for soil remediation and public health interventions. The study emphasizes the necessity of ongoing monitoring and protective measures to mitigate the health risks associated with heavy metal exposure from soil contamination.